Quantification of economically feasible mitigation potential from agriculture, forestry and other land uses in Mexico - Sapkota, Tek Bahadur; Dittmer, Kyle M.; Ortíz Monasterio, Jose Iván; Mathivanan, Gokul Prasad; Sonder, Kai; Leyva, Juan Carlos; García, Miguel Angel; Monroy, Diana Ysimoto; Shelton, Sadie W.; Wollenberg, Eva Karoline (Informa UK Limited, 2022)
Countries often lack methods for rapidly, but robustly determining greenhouse gas (GHG) mitigation actions and their impacts comprehensively in the land use sector to support commitments to the Paris Agreement. We present rapid assessment methods based on easily available spatial data and adoption costs for mitigation related to crops, livestock and forestry to identify priority locations and actions. Applying the methods for the case of Mexico, we found a national mitigation potential of 87.88 million tons (Mt) CO2eq yr−1, comprising 7.91, 7.66 and 72.31 Mt CO2eq yr−1 from crops, livestock and forestry/agro-forestry, respectively. At the state level, mitigation potentials were highest in Chiapas (13 Mt CO2eq) followed by Campeche (8 Mt CO2eq). Eleven states had a land use mitigation potential between 2.5 to 6.5 Mt CO2eq, while other states had mitigation potentials of less than 2 Mt CO2eq. Mitigation options for crops and livestock could reduce 60% and 6% of the respective emissions. Mitigation options for forestry could reduce emissions by half. If properly implemented, mitigation potentials on cropland can be realized with net benefits, compared to livestock and forestry options, which involve net costs. The method supports science-based priority setting of mitigation actions by location and subsector and should help inform future policy and implementation of countries’ nationally determined contributions.